Faʿāliyyatu Istikhdāmi aṭ-Ṭarīqah aṣ-Ṣāmitah (Silent Way) bi Ḥarākati al-Aṣābiʿ fī Tanmiyyati Ḥifẓi al-Mufradāt li-Ṭālibāti al-Faṣl al-ʿĀsyir fī al-Madrasah al-ʿĀliyah al-Islāmiyyah al-Ahliyah "al-Amīn" Mojokerto - Jumiati Mulyaningsih; Fathur Rohman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This article examines the effectiveness of using the Silent Way Method with finger visualization in improving mufradat memorization in 10th grade students of MA. Al-Amin Mojokerto, this study aims to (1) determine the application of the Silent Way Method with finger visualization in improving mufradat memorization in 10th grade students of MA. Al-Amin Mojokerto; (2) Knowing the improvement of mufradat memorization using the Silent Way Method with finger visualization in 10th grade students of MA. Al-Amin Mojokerto; (3) Knowing the effectiveness of the silent teacher method (Silent Way) with finger visualization in improving mufradat memorization in grade 10 MA students. Al-Amin Mojokerto, the method used is Quantitative Experiment with tests, questionnaires, and interviews, then analyzed using the Man Whitney Test, The results of the study: (1) The silent teacher method (Silent Way) is a mufradat learning method where 90% of the time allocation students are asked to be silent, not to write, not to read and only focus on what the teacher gives to students, the silent teacher method (Silent Way) is implemented in the Evening Language activity/language class. (2) The use of the Silent Way Method with finger visualization supports students to be able to improve memorization of mufradat in grade 10 MA students. Al-Amin Mojokerto, as evidenced by the answers to the questionnaire and the results of the pre-test and post-test. (3) The silent teacher method (Silent Way) with finger visualization is effective in improving mufradat memorization in 10th grade students of MA. Al-Amin Mojokerto, as evidenced by the sig value, 0.00 < 0.05.